The minimum effective concentration (MEC90) of ropivacaine for ultrasound‐guided supraclavicular brachial plexus block. (4th March 2016) - Fang, G.; Wan, L.; Mei, W.; Yu, H. H.; Luo, A. L.
Summary: The aim of this study was to determine the minimum effective concentration of ropivacaine for ultrasound‐guided supraclavicular brachial plexus block. Fifty‐one patients undergoing arm surgery received double‐injection ultrasound‐guided supraclavicular block using ropivacaine 40 ml. The concentration of ropivacaine administered to each patient started at 0.225% and then depended on the response of the previous one, based on a biased coin design up‐and‐down sequential method. In case of failure, the ropivacaine concentration was increased by 0.025% w/v in the next subject. In the case of a successful block, the next patient was randomised to the same concentration or a concentration 0.025% w/v less. Success was defined as complete sensory blockade of the brachial plexus 30 min after the block together with pain‐free surgery. The minimum effective ropivacaine concentration in 90% of subjects was 0.257% w/v (95% CI 0.241–0.280%).